ROSUVASTATIN - THE MOST POTENT STATIN IN CARDIOVASCULAR DISEASE PREVENTION - A. E. Semenova; I. V. Sergienko (Евразийский Кардиологический Журнал)
Rosuvastatin is a statin with maximum hypolipidemic effect, to date, which makes it one of the most frequently prescribed lipid-lowering medications. The drug has been widely studied in large international randomized clinical trials and proven to be highly effective. Administration of rosuvastatin at doses of up to 40 mg/day allows to decrease low-density lipoprotein cholesterol (LDL-C) levels by 55-63%, triglyceride levels by 28% and to significantly increase the level of high-density lipoprotein cholesterol by 10-14%. The effectiveness of rosuvastatin for primary prevention of CV complications has been indicated in high and very high risk patients, as well as in intermediate-risk persons and patients with mildly elevated base LDL-C level. The ability of rosuvastatin to suppress the progression of atherosclerosis has been demonstrated by intravascular ultrasound of coronary arteries and by magnetic resonance imaging of carotid arteries. Rosuvastatin is a hydrophilic statin with high hepatoselectivity, low systemic bioavailability (very limited penetration of rosuvastatin into extrahepatic tissues and, hence, lower risk of myotoxicity) and minimal involvement of P450 cytochrome in its metabolism (mostly mediated by 2C9 enzyme), which provides for good tolerability of the drug. High hepatoselectivity and the absence of any significant interaction with cytochrome P450 system mitigate the likelihood of side effects and drug interactions. The above mentioned characteristics of rosuvastatin enable its effective and safe use in treating a wide range of patients.